2021
DOI: 10.1002/anie.202014718
|View full text |Cite
|
Sign up to set email alerts
|

Silver Single‐Atom Catalyst for Efficient Electrochemical CO2 Reduction Synthesized from Thermal Transformation and Surface Reconstruction

Abstract: We report an Ag1 single‐atom catalyst (Ag1/MnO2), which was synthesized from thermal transformation of Ag nanoparticles (NPs) and surface reconstruction of MnO2. The evolution process of Ag NPs to single atoms is firstly revealed by various techniques, including in situ ETEM, in situ XRD and DFT calculations. The temperature‐induced surface reconstruction process from the MnO2 (211) to (310) lattice plane is critical to firmly confine the existing surface of Ag single atoms; that is, the thermal treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(145 citation statements)
references
References 68 publications
2
134
0
Order By: Relevance
“…For example, Li et al deposited Ag single atoms on MnO 2 and found that Ag single atoms in Ag 1 /MnO 2 had a higher electronic density close to the Fermi level than Ag nanoparticles, which enabled them to reduce CO 2 to CO with a FE of 95.7% at À0.85 V vs. RHE. 119 Sun et al reported that Sn single atoms supported on oxygen-decient CuO could reduce CO 2 to ethylene with a FE of 48.5%, resulting from the lowered CO dimerization energy due to Sn doping. 120 The CO 2 RR is limited by the scaling relationship.…”
Section: +mentioning
confidence: 99%
“…For example, Li et al deposited Ag single atoms on MnO 2 and found that Ag single atoms in Ag 1 /MnO 2 had a higher electronic density close to the Fermi level than Ag nanoparticles, which enabled them to reduce CO 2 to CO with a FE of 95.7% at À0.85 V vs. RHE. 119 Sun et al reported that Sn single atoms supported on oxygen-decient CuO could reduce CO 2 to ethylene with a FE of 48.5%, resulting from the lowered CO dimerization energy due to Sn doping. 120 The CO 2 RR is limited by the scaling relationship.…”
Section: +mentioning
confidence: 99%
“…Since the concept of single-atom catalysis was firstly proposed by Zhang, Li, Liu et al in 2011 [1], considerable attention has been paid to this area because of its unique homogeneous structural characteristics of a single-atom (SA) active center and the excellent catalytic performance in heterogeneous catalysis [2][3][4][5][6][7][8][9][10]. Several reviews [11][12][13][14][15] have summarized the development of single-atom catalysts (SACs), the structure-function relationship between SACs and their catalytic performance, and the diverse applications of SACs in heterogeneous catalysis [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…After electrochemical reduction, the S 2p peak at 164 eV binding energy disappeared, indicating the reduction of metal mercaptan salts, while the Ag−S bonds appeared (peak at 161.44 and 162.54 eV), which results from the interaction of the cysteamine with the Ag surface [33]. When Ag-Cys was transformed into Ag-TC in electrochemical reduction, interactions between the ambient oxygen on the Ag-Cys surface and reduced thiols leads to the formation of −S−O− (peak at 169.3 eV) [43]. Figure 2(c) shows the X-ray absorption spectra of Ag foil, Ag-Cys, and Ag-TC.…”
Section: Materials Preparation and Characterizationmentioning
confidence: 99%